2010
DOI: 10.1080/10503307.2010.493539
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Helping Alliance Questionnaire-I in psychodynamic psychotherapy for major depression

Abstract: The psychometric properties of the Helping Alliance Questionnaire-I were analyzed at two times in short-term psychoanalytic supportive psychotherapy for outpatient depression. Exploratory factor analysis conducted in 142 patients generated a model that was confirmed in a different validation sample (n=106) using confirmatory factor analysis. Two factors were found to have satisfactory psychometric properties and a consistent structure over time: relationship and internal change. The authors conclude that repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
13
0
10

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 29 publications
5
13
0
10
Order By: Relevance
“…Das Konzept der Arbeitsallianz stellt ein zentrales Konzept der Psychotherapie dar, welchem unterschiedlichste Theorien und Überlegungen zugrunde liegen [1,2]. Zusammenfassend werden mit der therapeutischen Arbeitsallianz die kollaborativen Aspekte der unmittelbaren Patient-Therapeut-Interaktion hervorgehoben und das einvernehmliche Zusammenarbeiten in den Vordergrund gestellt [1,3].…”
Section: Introductionunclassified
See 3 more Smart Citations
“…Das Konzept der Arbeitsallianz stellt ein zentrales Konzept der Psychotherapie dar, welchem unterschiedlichste Theorien und Überlegungen zugrunde liegen [1,2]. Zusammenfassend werden mit der therapeutischen Arbeitsallianz die kollaborativen Aspekte der unmittelbaren Patient-Therapeut-Interaktion hervorgehoben und das einvernehmliche Zusammenarbeiten in den Vordergrund gestellt [1,3].…”
Section: Introductionunclassified
“…In den international publizierten Studien werden am häufigsten vier englischsprachige Fragebogen zur Messung der (Arbeits-)Allianz als Selbst-und Fremdeinschätzungsverfahren eingesetzt: California Psychotherapy Alliance Scale (CALPAS), Vanderbilt Psychotherapy Process Scale (VPPS), Working Alliance Inventory (WAI) und Helping Alliance Questionnaire (HAQ) [1,2]. Während die ersten drei Verfahren auf einer Vielzahl von theoretischen integrativen Überlegungen basieren, baut der HAQ vor allem auf psychodynamischen Konzepten auf.…”
Section: Introductionunclassified
See 2 more Smart Citations
“…However, additional 2 tests and ANOVA showed that there were no differences regarding technique, defense and outcome between the groups with or without medication. Finally, technique was limited to the supportive-expressive continuum, excluding other change mechanisms related to outcome such as alliance [29] and implicit relational processes like attunement [30,31] .…”
mentioning
confidence: 99%